2012
DOI: 10.1007/s11255-012-0199-8
|View full text |Cite
|
Sign up to set email alerts
|

Pathological implications of areas of lower enhancement on contrast-enhanced computed tomography in renal-cell carcinoma: additional information for selecting candidates for surveillance protocols

Abstract: Lower enhancement of the entire tumor at the point where hypodense tumor areas are more predominant on tomography is associated with higher nuclear grade and more advanced stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Previous reports have shown that CCRCC is a highly angiogenic and vascularized tumor ( 31 ). In addition, the differences in enhancement patterns between low- and high-grade CCRCCs have been proved to correlate to the hemodynamics and microvessel density (MVD) of individual RCC lesions ( 32 , 33 ). Ficarra et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have shown that CCRCC is a highly angiogenic and vascularized tumor ( 31 ). In addition, the differences in enhancement patterns between low- and high-grade CCRCCs have been proved to correlate to the hemodynamics and microvessel density (MVD) of individual RCC lesions ( 32 , 33 ). Ficarra et al.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that CCRCC is a highly angiogenic and vascularized tumor(31). In addition, the differences in enhancement patterns between low-and high-grade CCRCCs have been proved to correlate to the hemodynamics and microvessel density (MVD) of individual RCC lesions(32,33). Ficarra et al(34) validated that intratumoral necrosis as a prognostic factor is useful in the clinical management of CCRCC patients, which is recommended by the Mayo Clinic Stage, Size, Grade, and Necrosis (SSIGN) scoring system…”
mentioning
confidence: 99%
“…We have previously evaluated the reliability of computed tomography (CT) to predict nuclear grade in renal cell carcinoma [8]. In the present study we aimed to identify and quantify AAT and its compartments, as measured by CT, and determine their influence on histopathologic characteristics and outcomes of renal cell carcinoma in patients treated with radical or partial nephrectomy at a single tertiary care referral center in Mexico.…”
Section: Introductionmentioning
confidence: 99%